Are teachers 'same same but different'? – The meaning of career success across occupations. Issue 1 (1st January 2020) - Gubler, Martin; Eggenhofer-Rehart, Petra; Andresen, Maike; Mandel, Debbie; Mayrhofer, Wolfgang; Lehmann, Philip; Schleicher, Nanni Elisabeth; Schramm, Florian
ABSTRACT: What a 'successful career' means to teachers is little understood, although this would allow schools and educational governance alike to support teachers' development, and to reduce their attrition. This study examines how 240 school teachers from Germany, Austria and Switzerland conceptualize career success, as compared to 185 health-care/social workers and 125 information technology professionals. Using a cross-culturally validated, multidimensional scale, the authors find that teachers differ from other occupations in some, but not all, career success dimensions. Their findings underline the relevance of cross-occupational studies in research related to teachers' career development, and they suggest new levers for increasing teachers' motivation, creating more effective developmental opportunities for them, and – ultimately – reducing teacher attrition.